2016
DOI: 10.4174/astr.2016.90.5.279
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative indocyanine green angiography for the objective measurement of blood flow

Abstract: PurposeIntraoperative assessment of tissue perfusion is important to predict wound healing or improvement of symptoms in patients with peripheral arterial disease (PAD) or vascular trauma. There is no widely accepted standard for intraoperative measurement of tissue perfusion. Here, we report the use of indocyanine green (ICG)-based angiography to determine the blood flow in patients with PAD and vascular trauma.MethodsThe SPY fluorescent imaging system was utilized. A dose of 3–5 mL of ICG (2.5 mg/mL) was inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…However, the limitation of in vivo fluorescence imaging to small animals has prevented similar quantification in large animal models and humans in the same capacity. The recent development of portable NIR imaging devices such as the SPY and Fluobeam [25,26] have allowed us to confirm previous studies on residual plasma flow in https://doi.org/10.1371/journal.pone.0244236.g005…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, the limitation of in vivo fluorescence imaging to small animals has prevented similar quantification in large animal models and humans in the same capacity. The recent development of portable NIR imaging devices such as the SPY and Fluobeam [25,26] have allowed us to confirm previous studies on residual plasma flow in https://doi.org/10.1371/journal.pone.0244236.g005…”
Section: Discussionsupporting
confidence: 77%
“…However, the limitation of in vivo fluorescence imaging to small animals has prevented similar quantification in large animal models and humans in the same capacity. The recent development of portable NIR imaging devices such as the SPY and Fluobeam [ 25 , 26 ] have allowed us to confirm previous studies on residual plasma flow in swine [ 6 ] move beyond prior studies to evaluate human blood flow in situ . This technology has demonstrated herein that 70% of human subjects with an extremity tourniquet in place also exhibit residual plasma flow and this flow directly correlated with MAP and BMI in volunteers.…”
Section: Discussionsupporting
confidence: 52%
“…x 13.5 cm 2 , with image sequences at 3.75 to 30 frames per second depending on recording time ranging from 30 seconds to 4.5 minutes. 13,14 From this, values such as ingress, ingress rate (rate at which fluorescence intensity increases on imaging field), peak perfusion (i.e. max intensity), egress, and egress rate are quantitatively determined while simultaneously displaying qualitative visual results.…”
Section: Discussionmentioning
confidence: 99%
“…ICG is usually used to directly measure the actual functional state of the liver [17]. Recently, ICG has been widely used to capture changes in intestinal ischemia [18, 19]. Ishizuka et al reported that using ICG in patients with nonocclusive mesenteric ischemia could facilitate proper removal of the ischemic intestine [20].…”
Section: Discussionmentioning
confidence: 99%